2020
DOI: 10.17645/pag.v8i1.2540
|View full text |Cite
|
Sign up to set email alerts
|

How Do Populist Voters Rate Their Political Leaders? Comparing Citizen Assessments in Three Jurisdictions

Abstract: Drawing from the field of management studies, we explore how a sample of voters in the United States, Canada, and the United Kingdom use a leader character framework to judge political leadership. We ask, how do voters actually assess the character of their current leaders? And, in light of the populist zeitgeist, do people who hold a populist attitude differ markedly in how they judge the character of political leaders? Our results show that voters generally consider character important. However, voters who l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Populists in all three jurisdictions believe that leader character matters much less than in the case of ordinary citizens, who clearly place more value on the importance of leader character. This finding is important for understanding how populist voters generally evaluate politicians, and why they may be drawn to some leaders over others (Seijts & de Clercy, 2020).…”
Section: Leadership and Populism In North America Or As Compared Witmentioning
confidence: 90%
See 1 more Smart Citation
“…Populists in all three jurisdictions believe that leader character matters much less than in the case of ordinary citizens, who clearly place more value on the importance of leader character. This finding is important for understanding how populist voters generally evaluate politicians, and why they may be drawn to some leaders over others (Seijts & de Clercy, 2020).…”
Section: Leadership and Populism In North America Or As Compared Witmentioning
confidence: 90%
“…In "How Do Populist Voters Rate Their Political Leaders? Comparing Citizen Assessments in Three Jurisdictions," we set out to explore how a sample of voters in the US, Canada, and the United Kingdom use a leader character framework to assess the character of some contemporary national leaders (Seijts & de Clercy, 2020). In probing whether citizens who lean toward populism view character the same as ordinary voters, we find these groups are quite different.…”
Section: Leadership and Populism In North America Or As Compared Witmentioning
confidence: 99%
“…The response options ranged from not at all (1) to a great extent (5); the midpoint of the scale was somewhat (3). These measures are similar to those used by Seijts and de Clercy (2020); Seijts et al (2018). All items we used in this study are shown in supplemental .…”
Section: Methodsmentioning
confidence: 99%
“…Values act as deep-seated beliefs people hold about what is morally right or wrong. Character is, in short, a habit of being—a set of observable behaviors—anchored in a set of virtues, personality traits, and values that facilitate human excellence and produce personal and social betterment (Crossan et al, 2017; Seijts & de Clercy, 2020).…”
Section: Leader Charactermentioning
confidence: 99%